Bacteremia, Causative Agents and Antimicrobial Susceptibility Among HIV-1–infected Children on Antiretroviral Therapy in Uganda and Zimbabwe - Musiime, Victor; Cook, Adrian; Bakeera-Kitaka, Sabrina; Vhembo, Tichaona; Lutakome, Joseph; Keishanyu, Rosette; Prendergast, Andrew J.; Lubwama, Sam; Robertson, Val; Hughes, Peter; Nathoo, Kusum; Munderi, Paula; et al. (The Pediatric infectious disease journal, 2013)
Bacteremia is common in HIV-infected children in Africa, including after start of antiretroviral therapy (ART), but there are limited data on causative pathogens and their antimicrobial sensitivity patterns in this population. Methods: We analyzed data on blood cultures taken from HIV-infected children developing acute febrile illness after enrollment to the Antiretroviral Research for Watoto (ARROW) clinical trial in Uganda and Zimbabwe. Patterns of bacterial pathogens and their antimicrobial susceptibilities were determined and bacteremia rates calculated over time from ART initiation. Results: A total of 848 blood cultures were obtained from 461 children, of which 123 (14.5%) from 105 children (median age 3.5 years, 51% girls) were culture positive, including 75 (8.8%) with clearly pathogenic organisms. The event rates for positive cultures with clearly pathogenic organisms after 0–1, 2–3, 4–11 and ≥12 months on ART were 13.3, 11.4, 2.1 and 0.3 per 1000 person-months of follow-up, respectively. The pathogens isolated (n; %) were Streptococcus pneumoniae (36; 28.3%), Staphylococcus aureus (11; 8.7%), Klebsiella pneumoniae (6; 4.7%), Pseudomonas aeruginosa (6; 4.7%), Salmonella spp (6; 4.7%), Escherichia coli (5; 3.9%), Haemophilus influenzae (1; 0.8%) and fungal spp (4; 3.1%). Other bacteria of doubtful pathogenicity (n = 52; 42%) were also isolated. Most isolates tested were highly (80–100%) susceptible to ceftriaxone, cefotaxime and ciprofloxacin; very few (~5%) were susceptible to cotrimoxazole; S. pneumoniae had high susceptibility to amoxicillin/ampicillin (80%). Conclusions: Rates of proven bacteremia were >20-fold higher immediately after starting ART compared with 12 months later in African HIV-infected children. S. pneumoniae was most commonly isolated, suggesting need for pneumococcal vaccination and effective prophylactic antibiotics.